Method of manufacturing reinforced concrete floor slabs using non-removable void formers - Pushkarev, B A; Burenina, N B (Journal of physics. Conference series, 2021)
The article provides a critical analysis of the work on the manufacture of monolithic reinforced concrete, relying on the contour, hollow floor slabs using box-shaped, spherical and tubular hollow-formers. The paper proposes a method of manufacturing monolithic reinforced concrete hollow floor slabs based on the contour using circular tubular polyethylene cardboard holders of rectangular or square shape in plan. The subject of the research is a method of continuous production of reinforced concrete floor slabs with round voids based on the contour using non-removable void formers, their technical and economic efficiency of solutions to reduce the weight of monolithic floor slabs by reducing the resources for their production. The technical and economic feasibility of manufacturing monolithic reinforced concrete floor slabs based on the contour with the use of non-retrievable void formers from round pipes of square and rectangular shape in plan has been substantiated. Materials for the manufacture of void former are proposed. The technical result has been determined - the maximum weight reduction of the proposed hollow core slabs compared to solid slabs.